Herpetic Neuralgia After Inactivated Covid-19 Vaccination : A Case Report - Rizaldy Taslim Pinzon; Hillary Shelyn Harsono (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT The COVID-19 pandemic has made prevention procedures against the rapidly spreading infection a top priority. Inactivated COVID-19 vaccines have been developed and authorized for use in some countries including Indonesia, where the Sinovac vaccine has been distributed to health care workers and the elderly. There have been no reports of herpes zoster reactivation after the Sinovac vaccine in Indonesia yet. Advanced age may be a risk factor in reduction of cell-mediated immunity that related to VZV reactivation.However, this article reports an unusual case of varicella zoster virus (VZV) reactivation in a patient who received the COVID-19 vaccine. This is the first case of VZV reactivation following Sinovac COVIDâ€19 vaccination. It is very difficultÂ  to establish a straightforward relationship between herpes zoster and inactivated COVIDâ€19 vaccine, immune dysregulation created by the vaccine may play a role in the reactivation of latent VZV infection in the current case. There is a need for further review and studies in the future.